Analisis Penerapan Tax Planning atas Biaya Kesejahteraan Karyawan dan Dosen di Perguruan Tinggi STIE Ahmad Dahlan Jakarta - Erion Erion; Irma Novida (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
This study uses a comparative descriptive analysis by analyzing and processing the data of financial statements and fiscal reports. It aims to analyze the benefits of in this part you need to explain “how to analyze tax planning implementation which can minimize the company tax burden. Data types used are primary and secondary data. The resource of the data is compiled from finance and other related department. This research had been held in higher education “X”. The data collection was done by interviewing, documenting and doing library research. Based on the research result, it can make conclusion that the institution has implemented tax planning well, that is by maximizing deductible expenses of employee benefits to deduct the company gross income so that it can minimize company tax burden without violating any prevailing laws.